A 3D computational method for determination of pores per inch (PPI) of porous structures. (March 2023) - Jamshidi, Farshid; Kunz, Willfried; Altschuh, Patrick; Lu, Tianyu; Laqua, Matthieu; August, Anastasia; Löffler, Frank; Selzer, Michael; Nestler, Britta
Abstract: Due to their special and unique morphology, porous materials have distinctive properties that make them interesting in several sciences and industries. In industrial applications, a popular parameter to characterize the structure of porous materials is the number of pores per inch (PPI). In this work, we implement a computational algorithm in three-dimensional space to determine the PPI number of a porous structure. The algorithm is composed of different steps: segmentation of pore space using a marker-based watershed algorithm, counting the number of pores and eventually calculating the PPI number. To characterize open-cell porous structures according to their PPI values, we generate three types of them. Firstly, an aligned porous structure with a known number of pores is synthetically generated. Excellent agreement between computational results and known values validates our PPI determination algorithm. Secondly, synthetic isotropic/anisotropic porous structures based on Voronoi tessellation (VT) are studied. Finally, we apply the algorithm to the digital twins of real metal foams. The validated proposed approach with reproducible results serves as a unique standard tool to determine the PPI value, and we discuss that it is more precise than conventional two-dimensional methods that are widely used in industry. Graphical abstract: